SISTEM INFORMASI DATA ALAT TULIS KANTOR PT. MITRANIAGA DISTRIBUSINDO KEDUNG HALANG BOGOR - Rukmana, Tedy; Rachmawati, Fitria (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2021)
To facilitate the process of requesting office stationery by designing a web application so that the process of requesting office stationery can be faster and controlled, thus each unit can submit requests for office stationery by accessing the web for requesting office stationery online. The formulation of the problem in this study is how the data collection system for Office Stationery PT. Mitraniaga Distribution of Kedung Halang Bogor which is currently running?. This study aims to create a data collection system for Office Stationery PT. Mitraniaga Distribution of Kedung Halang Bogor which is currently running?. The research method used is using the waterfall. Based on the results of the analysis of the demand for office stationery information systems, it can be concluded that with this office stationery request system, it can facilitate employees or staff in the process of requesting office stationery at PT. Mitraniaga Distribution, Kedung Halang, Bogor.